(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the quality of life (QoL) and identify related factors in patients with brain metastases from lung cancer undergoing whole-brain radiotherapy (WBRT) at the General Radiotherapy Department, Nghe An Oncology Hospital. Methods: A prospective, pre-post interventional study was conducted. Out of the initial eligible cohort, 32 lung cancer patients with brain metastases survived and completed 10 sessions of WBRTalong with a 1-month post-treatment follow-up. QoL was assessed at baseline and 1 month post-WBRT using the EORTC QLQ-C30 questionnaire and the brain cancer-specific module EORTC QLQ-BN20. To address multi-testing issues across various QoL dimensions, individual p-values were interpreted strictly as exploratory analyses Results: The analyzed population consisted of 87.5% males and 12.5% females, with 74.9% of patients aged 50–69 years. One month after WBRT, exploratory analyses demonstrated a positive trend in QoL scores among the survivors. The global QoL score increased from 22.8 to 43.6 (p < 0.001). Brain tumor-related symptoms also decreased: headache fell from 59.3% to 37.5%, nausea from 6.25% to 3.1%, seizures from 9.3% to 3.1%, paralysis from 21.8% to 18.7%, and severe pain from 9.6% to 3.9%. Conclusions: In the short term, whole-brain radiotherapy combine with supportive care serves as an effective palliative approach, improving quality of life and alleviating focal neurological symptoms in this highly selected cohort of surviving patients.